Distance Learning: Implementation in Langkat Elementary School during the Covid-19 Pandemic - Salim, Salim; Zulaika, Zulaika; Miranda, Nanda; Amin, Askur (Tarbawi, 2021)
This study aims to explore the implementation of distance learning in elementary schools during the Covid-19 pandemic. Case studies are used as research methods with qualitative approaches. The informant consists of teachers of Zahara Integrated Islamic Elementary School and teachers of State Elementary School 0505769 Sei Lepan Subdistrict Langkat North Sumatra Province, Indonesia. Research instruments were prepared around the implementation of distance learning in both schools. In-depth interviews are conducted to dig up information and check the truth. The results revealed the lack of parents in facilitating online learning, so that the implementation of learning is done offline outside the school environment consisting of four study groups, and each study group maximum of 5 students. However, there are problems faced by teachers during the learning process, namely: time management and administration such as learning schedules and learning implementation plan sheets, weekly attendance, and monthly attendance that must be submitted monthly to the education office. This research recommendation is for the number of students in the study group to be increased to 10 students with attention to health protocols and available resources.